Characterizing the delays in adequate thromboprophylaxis after TBI. Issue 1 (10th May 2021) - Dhillon, Navpreet K; Hashim, Yassar M; Berezin, Naomi; Yong, Felix; Conde, Geena; Mason, Russell; Ley, Eric J
Abstract : Background: We sought to compare enoxaparin dosing for venous thromboembolism (VTE) prophylaxis in trauma patients with and without traumatic brain injury (TBI) to better understand the time and dose required to reach target anti-Xa levels. Our hypothesis was that patients with TBI have significant delays in the initiation of adequate pharmacological prophylaxis and require a higher enoxaparin dose than currently recommended. Methods: The medical records of trauma patients who received enoxaparin dosing based on anti-Xa trough levels between August 2014 and October 2016 were reviewed. Patients were included if their anti-Xa trough level reached the target range (0.1 IU/mL to 0.2 IU/mL). Results: A total of 163 patients had anti-Xa levels within the target range of which 41 (25.2%) had TBI. Patients with TBI had longer delays before initiating enoxaparin (7.5 days vs. 1.5 days after admission, p<0.01) and were more likely to receive unfractionated heparin prior to enoxaparin (46.3% vs. 11.5%, p<0.01). Anti-Xa levels reached the target range later in patients with TBI (11 days vs. 5 days after admission, p<0.01). Enoxaparin 40 mg two times per day was the median dose required to reach the target anti-Xa levels for both cohorts. VTE rates were higher among patients with TBI (22.0% vs. 9.0%, p=0.03). Four patients (9.8%) had progression of their intracranial hemorrhage prior to receiving enoxaparin, although none progressed during enoxaparin administration. Conclusion: Among patients with TBI who reached target anti-Xa levels, 11 days after admission were required to reach a median enoxaparin dose of 40 mg two times per day. Unfractionated heparin was used as pharmacological prophylaxis in about half of these patients. The delay in reaching the target anti-Xa levels and the use of unfractionated heparin likely contribute to the higher VTE rate in patients with TBI. Level of evidence: Level III, therapeutic.